Treatment outcomes of advanced digestive well-differentiated grade 3 NETs. Issue 8 (23rd June 2021) - de Mestier, Louis; Lamarca, Angela; Hernando, Jorge; Zandee, Wouter; Alonso-Gordoa, Teresa; Perrier, Marine; Walenkamp, Annemiek ME; Chakrabarty, Bipasha; Landolfi, Stefania; Van Velthuysen, Marie-Louise F; Kats-Ugurlu, Gursah; Caminoa, Alejandra; et al.
Abstract : There is no standardized treatment for grade 3 neuroendocrine tumors (G3 NETs). We aimed to describe the treatments received in patients with advanced G3 NETs and compare their efficacy. Patients with advanced digestive G3 NETs treated between 2010 and 2018 in seven expert centers were retrospectively studied. Pathological samples were centrally reviewed, and radiological data were locally reviewed. We analyzed RECIST-defined objective response (OR), tumor growth rate (TGR) and progression-free survival (PFS) obtained with first- (L1) or second-line (L2) treatments. We included 74 patients with advanced G3 NETs, mostly from the duodenal or pancreatic origin (71.6%), with median Ki-67 of 30%. The 126 treatments (L1 = 74; L2 = 52) included alkylating-based ( n  = 32), etoposide-platinum ( n  = 22) or adenocarcinoma-like ( n  = 20) chemotherapy, somatostatin analogs ( n  = 21), targeted therapies ( n  = 22) and liver-directed therapies ( n  = 7). Alkylating-based chemotherapy achieved the highest OR rate (37.9%) compared to other treatments (multivariable OR 4.22, 95% CI (1.5–12.2); P  = 0.008). Adenocarcinoma-like and alkylating-based chemotherapies showed the highest reductions in 3-month TGR ( P  < 0.001 and P  = 0.008, respectively). The longest median PFS was obtained with adenocarcinoma-like chemotherapy (16.5 months (9.0–24.0)) and targeted therapies (12.0 months (8.2–15.8)), while the shortest PFS was observed with somatostatin analogs (6.2 months (3.8–8.5)) and etoposide-platinum chemotherapy (7.2 months (5.2–9.1)). Etoposide-platinum CT achieved shorter PFS than adenocarcinoma-like (multivariable HR 3.69 (1.61–8.44), P  = 0.002) and alkylating-based chemotherapies (multivariable HR 1.95 (1.01–3.78), P  = 0.049). Overall, adenocarcinoma-like and alkylating-based chemotherapies may be the most effective treatments for patients with advanced G3 NETs regarding OR and PFS. Etoposide-platinum chemotherapy has poor efficacy in this setting.